Territory and pandemic - Fedele, Javier (Universidad Nacional del Litoral, 2020)
Based on reflections on the new context generated by COVID-19, this article considers public policies and establishes their possible guidelines. In this field, a strategic approach to social and urban organizational structures is essential. Afterwards, the correspondence of this pandemic context with the urban situation and their challenges is analyzed. The socio-economic dynamics and the high interdependence of urban territories expose them to the current vulnerability. Some of the topics raised in recent debates are problematized: the density question, the public space vacuum and the insufficiency of private space, among others. Distributed densities, designed flexibilities and modulated risks are postulated as urban strategies in this context, trying to gather the first reactions in a set of strategically oriented actions. All reflection is framed according to the problems of local government, proposing approaches and consistent guidelines to address urban plans and projects.